Basic Demographic Parameters Help Predict Outcomes in Patients Hospitalized With COVID-19 During the First Wave of Infection in West Texas. (October 2020) - Ali, Kiran; Rao, Sanjana; Dennis, Jeff; Berdine, Gilbert; Test, Victor; Nugent, Kenneth
The severity of COVID-19 ranges from asymptomatic subclinical infections to severe acute respiratory failure requiring mechanical ventilation. Patients admitted to the hospital have increased mortality rates and patients requiring intensive care have significantly increased mortality rates. Multiple factors influence these outcomes. This study used simple demographic information available on admission to evaluate possible associations between these variables and outcomes, including mortality and length of stay. Clinical outcomes in 63 patients admitted to a tertiary care hospital in West Texas were reviewed. Older patients, patients admitted from nursing homes, and patients admitted to medical intensive care units had increased mortality. Unadjusted analysis indicated that males had increased mortality. Adjusted analysis indicated that males spent nearly 5 days longer in the hospital than females. In summary, age, chronic illness requiring nursing home placement, and acute severe illness requiring intensive care unit admission identify patients with worse prognoses. In addition, males will likely have a longer length of hospital stay.